2019
DOI: 10.1016/j.psychres.2019.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Low serum brain-derived neurotrophic factor is associated with suicidal ideation in major depressive disorder

Abstract: The "neurotrophic hypothesis of depression" posits that low levels of brain-derived neurotrophic factor (BDNF) are associated with Major Depressive Disorder (MDD). Low levels of BDNF have also been found in individuals with suicide attempts, in MDD or other disorders, suggesting that low BDNF may also be associated with suicidality. We assessed serum BDNF in 68 physically healthy and unmedicated (for at least 6 weeks) MDD subjects, who expressed no suicidal ideation (NSI; N=40) or endorsed suicidal ideation (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 46 publications
0
13
0
4
Order By: Relevance
“…In addition, evidence that reduced neurotrophic factor levels are tightly linked with neuronal atrophy in certain brain areas in individuals with MDD, such as the PFC and the hippocampus (Duman and Monteggia, 2006), led to the neurotrophic hypothesis of depression. Interestingly, in MDD patients with suicidal ideation, serum BDNF levels are significantly lower than MDD patients with no suicidal ideation (Khan et al, 2019), which suggests that serum BDNF levels may have a complex relationship with MDD symptoms.…”
Section: Astrocytes Influence Mood Disorders Through Interaction Withmentioning
confidence: 99%
“…In addition, evidence that reduced neurotrophic factor levels are tightly linked with neuronal atrophy in certain brain areas in individuals with MDD, such as the PFC and the hippocampus (Duman and Monteggia, 2006), led to the neurotrophic hypothesis of depression. Interestingly, in MDD patients with suicidal ideation, serum BDNF levels are significantly lower than MDD patients with no suicidal ideation (Khan et al, 2019), which suggests that serum BDNF levels may have a complex relationship with MDD symptoms.…”
Section: Astrocytes Influence Mood Disorders Through Interaction Withmentioning
confidence: 99%
“…Many studies have indicated that BDNF expression is associated with the severity of illness in depressed patients, including suicidal ideation 41 and executive dysfunctions. 42 Therefore, BDNF has become a key biomarker for depression disorder.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF has been suggested to be a potential indicator of ECT response [60]. Low levels of BDNF have been suggested to be associated with suicidality in patients with depressive disorders [62,63]. The results of these changes in BDNF were relatively consistent in adults with MDD.…”
Section: The Cytokines In Neuroinflammationmentioning
confidence: 96%